2010
DOI: 10.1016/s1836-9553(10)70049-7
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability for measurement of passive physiological range of motion of upper extremity joints is better if instruments are used: a systematic review

Abstract: Inter-rater reliability for the measurement of passive movements of upper extremity joints varies with the method of measurement. In order to make reliable decisions about joint restrictions in clinical practice, we recommend that clinicians measure passive physiological range of motion using goniometers or inclinometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…Assessment of range of motion (goniometry) and strength (manual muscle testing and/or dynamometry) were used frequently by respondents in this study. However, additional assessment, such as the Michigan Hand Questionnaire 67 , DASH 45 or Jebsen-Taylor Hand Function test 44 , is required to quantify the functional implications of these conditions 20,22,23,29,30 . The findings from this study, however, showed that assessments addressing activity and participation were used infrequently or not at all.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of range of motion (goniometry) and strength (manual muscle testing and/or dynamometry) were used frequently by respondents in this study. However, additional assessment, such as the Michigan Hand Questionnaire 67 , DASH 45 or Jebsen-Taylor Hand Function test 44 , is required to quantify the functional implications of these conditions 20,22,23,29,30 . The findings from this study, however, showed that assessments addressing activity and participation were used infrequently or not at all.…”
Section: Discussionmentioning
confidence: 99%
“…It would be expected that assessing clients with nerve injury would require measurement tools to assess range of motion, strength, sensibility ( 19,23,[29][30][31][32] . However, the respondents in this study used these assessments infrequently or not at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accessory mobility testing is an integral part of manual therapy [30] and is assessed passively by an external force that allows the physical therapist assess joint restrictions or increased movement of a joint [30] [31]. The passive movement of the joint promotes an environment conducive to the physical therapist acknowledging an end-feel, [31].…”
Section: /28mentioning
confidence: 99%
“…49,50 It is important to identify contractures to implement appropriate treatments and monitor change. 51 Passive joint range of motion can be measured quantitatively with a goniometer 52 however, for the purposes of this data set the committee recommends the use of visual and physical assessment to determine the loss in joint range of motion. Only obvious loss in joint range of motion that can be readily seen or easily felt should be recorded as a contracture.…”
Section: Contracturementioning
confidence: 99%